Ayudenme por favor
Adjuntos:
![](https://es-static.z-dn.net/files/d4a/9d54921aafdf2ae4e20ff578fcfd7dcc.jpg)
Respuestas a la pregunta
Contestado por
1
Respuesta:
Explicación paso a paso:
A={(2(3)ΨΨ)(ΨΨ)-(
ΨΨ}2(1)ΨΨ
A={(6ΨΨ)(ΨΨ)-ΨΨ}2ΨΨ
A={6-ΨΨ}2ΨΨ
A=12-2
Contestado por
0
Respuesta:
A= 10
(6 x 1 - 1) 2
( 6-1)2
( 5)2
10
Espero te sirva
Otras preguntas
Psicología,
hace 7 meses
Religión,
hace 7 meses
Ciencias Sociales,
hace 7 meses
Ciencias Sociales,
hace 1 año
Matemáticas,
hace 1 año
Salud,
hace 1 año